A New Learned Construction Of Indonesian Networks (Online) At Elementary School Sutomo 1 Medan - Christinna, Mery; Saragih, Erikson (CV. Inara, 2022)
A current online learning applied, done to suppress Covid-19 spread rates. An online learning system is implemented through a Personal Computer (PC) or laptop connected to an internet network connection. This study uses a descriptive qualitative approach. The purpose of this study was to describe the construction of online learning in the field of Indonesian language studies at SD Sutomo 1, Medan. The research subjects were taken as many as 9 people, namely 3 Indonesian language teachers, 3 parents, and 3 students who attend SD Sutomo 1. The object of research is teaching material in online learning which includes writing, reading, and listening. The data determination technique used the Simple Random Sampling method. The research method is a literature study. The data analysis technique used is by collecting data from interviews, observations, documentation, and other sources. The result of this study is that online learning is not as good as face-to-face due to the lack of direct interaction between teachers and students. The conclusion of this research isSUTOMO 1 Elementary School chose to continue using the 2013 national curriculum because the school wanted to continue to provide maximum learning services to students even through online learning.